The vibration of rectangular orthotropic plate with massive inclusions - Sukhorolsky, Mykhailo; Shopa, Tetyana (Computer Assisted Methods in Engineering and Science, 2022)
The problem on proper and forced vibrations of the loosely leant rectangular orthotropic plate with massive circular inclusion is considered in the paper. The flexure of the plate is described by modified equations of Timoshenko's theory of plates. Numerical solution of the problem is found by the indirect method of boundary elements based on the sequential approach to constructing generalized functions and on collocation method. The problem can be generalized on the case of arbitrary located inclusion and the arbitrary number of them. The influence of the mass of the massive circular inclusion on the proper frequencies of the plate is investigated.